Eating as an Automatic Behavior - Deborah A. Cohen, MD, MPH; Thomas A. Farley, MD, MPH (Centers for Disease Control and Prevention, 2008)
The continued growth of the obesity epidemic at a time when obesity is highly stigmatizing should make us question the assumption that, given the right information and motivation, people can successfully reduce their food intake over the long term. An alternative view is that eating is an automatic behavior over which the environment has more control than do individuals. Automatic behaviors are those that occur without awareness, are initiated without intention, tend to continue without control, and operate efficiently or with little effort. The concept that eating is an automatic behavior is supported by studies that demonstrate the impact of the environmental context and food presentation on eating. The amount of food eaten is strongly influenced by factors such as portion size, food visibility and salience, and the ease of obtaining food. Moreover, people are often unaware of the amount of food they have eaten or of the environmental influences on their eating. A revised view of eating as an automatic behavior, as opposed to one that humans can self-regulate, has profound implications for our response to the obesity epidemic, suggesting that the focus should be less on nutrition education and more on shaping the food environment.